STRATEGI PENGEMBANGAN PARIWISATA DI KABUPATEN TULUNGAGUNG - Ida Gemawati Monda; Imam Fachruddin (Universitas Kadiri, 2019)
This study aims to analyze the strategies that have been implemented by the local government of Tulungagung District in developing tourism. This study uses a qualitative approach to interpret the experiences of informants related to tourism development activities. At least, the strategy that has been used is to synergize all related institutions and optimize the role of tourism villages. The inhibiting factor that emerges is the geographical location of tourist attractions that are difficult and are disaster-prone areas, while a significant supporting factor is the presence of social media that can bring tourists without requiring substantial resources.